Energy potential from municipal solid waste in Perlis - Nur Wahidah Mardhiah Zullkiplee (School of Environmental Engineering University Malaysia Perlis, 2011)
The amount of municipal solid waste (MSW) that generated in Perlis is about 205 tons/day. The existing landfill currently are not properly managed due to the limited land availibility in this state. Alternatively, thermal treatment of MSW should be implemented in view of advantages in energy recovery. Solid waste will combusted to generated energy by using this technology. A study was conducted to estimate the energy content of MSW based on its physical composition , bomb calorimeter and proximate analysis. From the characterization of MSW, the main components of Perlis MSW were found to be glass, paper and plastic, which made up approximately 64% of the MSW. Calorimetric analysis revealed that the average energy content of MSW based on its physical composition is 2954kcal/kg and the energy potential assessed to be 859kW/day.